Prevalence and incidence rate of musculoskeletal disorders in elite female handball players: a systematic review - Goyal, K.; Balodhi, A.; Manglik, P.; Gupta, S.; Asif, M. (International Journal of Health Sciences & Research)
Introduction: Handball is perilous Olympic contact sports played on land. It is considered risky due to its multifactorial and tactile components along with negligence towards the use of protective gear. The game, despite having an offensive manoeuvre, has gained a great substantial popularity amidst the youth making it the second most popular team sport at the Olympics (2016). Musculoskeletal disorders are common to the sport. They are the leading contributor to disability worldwide and significantly limit mobility and dexterity, leading to early retirement from game. Purpose of Study: The purpose of this study is to review a series of articles (n=19) to understand the prevalence and incidence rate of musculoskeletal disorders in elite female Handball players. Type of Study: The following is a Systematic Literature Review. Result: The research provides an establishment of the fact that the incidence and prevalence of musculoskeletal disorders are higher in female handball team players.